Pengaruh Jumlah Anakan Terhadap Pertumbuhan dan Hasil Beberapa Genotip Sorgum (Sorghum bicolor (L.) Moench) Lokal Jawa Timur: Effect of Number of Tillers on Growth and Yield of Several Genotypes of Local Sorghum (Sorghum bicolor (L.) Moench) East Java - Nasihin, Muhammad; Sulistyawati, Sulistyawati; Arifin, Ahmad Zainul (Journal of Applied Plant Technology, 2022)
Sorghum is one type of cereal plant that is easy to cultivate. The use of local varieties in crop cultivation is very good because it can reduce the potential for crop failure. One way to increase crop productivity is by regulating plant density. The aim of the study was to determine the right number of tillers to optimize growth and yield of sorghum from several local genotypes of East Java. The local genotypes used were Sb.Pas, Sb.Spg1 and Sb.Lmg2. The design used was a randomized block design with 9 treatments and 3 (three) replications. The data obtained from the study were analyzed using Variety Analysis, if there was a significant effect, then proceed with the 5% BNT test. The results of the analysis showed significant differences in all components of plant growth and yield observations except for the total dry weight of the plant. While the use of the same genotype showed results that were not significantly different. Better results were obtained with Sb.Spg1 + 3 treatment on the observation of the number of leaves and stem diameter, and Sb.Pas + 2 on the observation of plant height. Observation of the results of the treatment with fewer tillers gave better results in the observation of individual plants but not significantly different from the observations of clump-1 and plot-1. The results of the growth and production of sorghum are influenced by the genotype of the plant, the environment and the attack of Plant Pest Organisms , especially leaf rust disease which is the main disease in sorghum plants.